Cellular senescence in the innervated niche modulates cancer-associated pain: an emerging therapeutic target? - Antonangeli, Fabrizio; Arcuri, Edoardo; Santoni, Angela (Frontiers in Immunology, 2025)
Crosstalk between cancer cells and the nervous system establishes the so-called “innervated niche”. This component of the tumor microenvironment (TME) influences tumor progression and variably regulates the genesis and maintenance of cancer-related pain. Senescence is a cellular stress response emerging as a hallmark of cancer and aging. Through the inflammatory secretome referred to as the senescence-associated secretory phenotype (SASP), senescent cells execute immunomodulation and tissue remodeling, participating in many physio-pathological processes. As inflammation is a key determinant of the TME as well as of neuropathies, in this review article we try to outline the possible role of senescence in the innervated niche. We argue that senescence can contribute to neuroinflammation, which is nowadays recognized as the initial factor triggering both cancer and non-cancer pain, by boosting local inflammation in the TME. At the same time, senescent cells can become targetable elements of the innervated niche to control cancer pain. We describe how the immune system supports the resolution of pain, and we suggest the possibility of harnessing natural killer (NK) cells, the prototype of innate immunity lymphocytes, for therapeutic approaches aimed at pain relief.